Mini-invasive Aortic Surgery: Personal Experience. Issue 5 (September 2014) - Spinelli, Francesco; Stilo, Francesco; La Spada, Michele; Benedetto, Filippo; De Caridi, Giovanni; Barillà, David; Giardina, Massimiliano; David, Antonio
Objective: In this study, we retrospectively evaluated our experience in minilaparotomy (MINI) and compared the results with conventional open repair (OPEN). Methods: From January 2005 to December 2012, we surgically treated 234 consecutive patients with elective infrarenal abdominal aortic aneurysms, 195 men and 39 women, with a mean age of 74 years. Inclusion criteria for MINI were not ruptured abdominal aortic aneurysm, increased surgical risk, anatomical limits for endovascular repair, no previous surgical invasion of the abdominal cavity, and no requirement for concomitant abdominal surgical invasion. Surgical treatment was OPEN in 113 patients (48.3%) and MINI through an 8- to 14-cm incision in 121 patients (51.7%). Epidural anesthesia has been added in 26.5% and in 19.3% of the MINI and OPEN patients, respectively. Mortality, complications, aortic clamping time, operative time, need for postoperative morphine therapy, time to solid diet, and length of hospital stay were registered. Results: The MINI has been performed in all patients selected, with 72 aortoaortic grafts and 49 aortobisiliac grafts. Early mortality was 1.6% versus 3.5% ( P > 0.5); 1-, 3-, and 5-year mortality were 7% versus 9%, 19% versus 22%, and 29% versus 34% ( P > 0.5); complications were 12.2% versus 26.6% ( P > 0.05); mean (SD) clamping time was 48 (12) versus 44 (14) minutes ( P > 0.5); mean (SD) operative time was 218.72 (41.95) versus 191.44 (21.73) minutes ( P > 0.025); mean (SD) estimated intraoperative blood loss was 425.64 (85.95) versus 385.30 (72.41) mL ( P > 0.1); mean (SD) morphine consumption in the group given epidural and the group not given epidural was 0 (2) and 2 (2) mg intravenously (IV) versus 2 (4) ( P < 0.5) and 4 (3) mg IV ( P > 0.1); mean (SD) ambulation was 2.1 (0.6) versus 4.1 (2.7) ( P < 0.5); mean (SD) time to solid diet was 2.1 (0.4) versus 3.5 (1.6) ( P < 0.5); and mean (SD) length of hospital stay was 4.9 (1.64) versus 7.35 (1.95) days ( P > 0.05), in the MINI and OPEN groups, respectively. Postoperative hernia at 3 years was 18% versus 23% in the MINI and OPEN groups ( P < 0.5), respectively. Conclusions: The MINI gives the patients a significantly shorter period of recovery with the quality and safety of the OPEN. This experience suggested extending the indication to all surgical candidates without local limitations.